HUBUNGAN KEPATUHAN PASIEN MENJALANI TERAPI HEMODIALISA DENGAN TINGKAT DEPRESI PASIEN GAGAL GINJAL KRONIK DI KLINIK RASYIDA MEDAN TAHUN 2015 - Jagentar P Pane (Elisabeth Health Jurnal, 2016)
Chronic renal failure or end stage renal disease (ESRD) is a progressive disorder of renal function and irreversible regardless of the cause. Renal replacement therapy consists of hemodialysis, peritoneal dialysis and kidney transplantation. Hemodialysis therapy is a renal replacement therapy is the most widely performed and the numbers from year to year continues to increase. Dialysis.Goal:The purpose of this study was to determine the relationship between adherence to undergo hemodialysis therapy with the level of depression in patients with chronic renal failure Rasyida Clinic Medan Year 2015.Chronic renal failure or end stage renal disease (ESRD) is a progressive disorder of renal function and irreversible regardless of the cause. Renal replacement therapy consists of hemodialysis, peritoneal dialysis and kidney transplantation. Hemodialysis therapy is a renal replacement therapy is the most widely performed and the numbers from year to year continues to increase. Dialysis.Goal:The purpose of this study was to determine the relationship between adherence to undergo hemodialysis therapy with the level of depression in patients with chronic renal failure Rasyida Clinic Medan Year 2015.Method:The study design with Analitik descriptive, cross-sectional method, sampling is done with purposive sampling. Samples are 69 respondents. Compliance questionnaire measuring devices and depression. Data analysis was performed using Chi-square analysis.Result: value of p = 0.023 (p <0.05). The figure indicates that there is a significant relationship between adherence variables undergo hemodialysis therapy with levels of depression patients with chronic renal failure. Based on the data obtained by processing the majority of respondents did not obey as many as 34 people (49.3%) and respondents were obedient as many as 35 people (50.7%) and respondents were depressed as many as 21 people (30.4%) and respondents who are not depressed as much as 48 people (69.6%).Method:The study design with Analitik descriptive, cross-sectional method, sampling is done with purposive sampling. Samples are 69 respondents. Compliance questionnaire measuring devices and depression. Data analysis was performed using Chi-square analysis.Result: value of p = 0.023 (p <0.05). The figure indicates that there is a significant relationship between adherence variables undergo hemodialysis therapy with levels of depression patients with chronic renal failure. Based on the data obtained by processing the majority of respondents did not obey as many as 34 people (49.3%) and respondents were obedient as many as 35 people (50.7%) and respondents were depressed as many as 21 people (30.4%) and respondents who are not depressed as much as 48 people (69.6%).